1979
DOI: 10.1084/jem.150.5.1108
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms in cell-mediated immune responses. VIII. Differential expression of I-region determinants by suppressor cells and their targets in suppression of mixed leukocyte reactions.

Abstract: The phenotypic expression of I-region determinants on cells producing and responding to MLR suppressor factor (MLR-TsF) was established in these studies. Alloantigen-activated MLR suppressor T cells (MLR-Ts), which produce MLR-TsF bearing gene products of the I-C subregion, were exposed to anti-I subregion sera and complement (C) before in vitro culture for MLR-TsF production. Suppressor activity was prevented by removal of cells bearing I-C determinants, whereas elimination of cells expressing I-A/B determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…These results are in agreement with the data on the same marker expression on a non-specific anti-H-2 suppressor T-cell-TsF producer (Rich & David 1979). The I-C expression seems to be the property of any MHC-induced T-suppressors independent of their antigenic specificity.…”
Section: Genetic "Interactional" Restriction Of the Sstc Functionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in agreement with the data on the same marker expression on a non-specific anti-H-2 suppressor T-cell-TsF producer (Rich & David 1979). The I-C expression seems to be the property of any MHC-induced T-suppressors independent of their antigenic specificity.…”
Section: Genetic "Interactional" Restriction Of the Sstc Functionsupporting
confidence: 91%
“…The requirement for identity in either the I-C subregion atone or the I-A -|-I-J -I-I-E complex between SSTC and the responders in MLC is indicative of dual recognition: SSTC interact with antigenic determinant by the antigen-specific receptors and, besides, they contact T-responders identical lo themselves in the indicated I-subregions. Requirements for suppressor-inhibited T cell homology in the I-C subregion (Rich et al 1979) or in one of the subregions (I-C or I-A) (Chensue et al 1983) were demonstrated in the other experimental systems.…”
Section: Genetic "Interactional" Restriction Of the Sstc Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…If these I-J-suppressor cells do indeed mask a Tc response to non-H-2 alloantigens, the interpretation of our earlier finding that pretreatment of a responder spleen cell population with an anti-Ia serum, which included a high titer of anti-I-J activity, and C led to significant primary anti-minor locus response was probably incorrect (16). As I-J-encoded determinants have been demonstrated on suppressor cells in a variety of systems (53)(54)(55), we interpreted the result as indicating that anti-Ia and C treatment removed a suppressor cell and thus facilitated a non-H-2 alloantigen-specific Tc response. It is possible that the suppressor expresses some Ia determinant(s) other than I-J, because the antiserum which was prepared in the mouse combination (B 10.HTT X A.TH)F1 anti-A.TL also contained strong anti-I-A k specificities.…”
Section: Discussionmentioning
confidence: 68%
“…Nonetheless, the H-2 complex is thought to control the functions, not of SSTC directly, but rather of their humoral factors, whose suppressive activity requires homology either in the I-J subregion (Pierres et al, 1979;Taniguchi & Tokuhisa, 1980) or in the KID region of the H-2 complex (Moorhead, 1979) between the factor and the acceptor T cells responsive to it. Besides, requirement for such a homology in the Z-C subregion has been shown where T cell proliferation in the mixed lymphocyte reaction (MLR) is inhibited by a factor from non-specific suppressor T cells induced with H-2 antigens (Rich et al, 1979). The function of anti-virus non-specific SSTC may be restricted by the D region of the H-2 complex (Humar & Bennett, 1977).…”
Section: Introductionmentioning
confidence: 99%